Comparison of Hospitalization Rates and Clinical Features Between Boys and Girls With Respiratory Syncytial Virus Infection - Uusitupa, Erika; Waris, Matti; Vuorinen, Tytti; Heikkinen, Terho (Wiley, 2026)
Background
Male sex is a well-known risk factor for respiratory syncytial virus (RSV) hospitalization in children, but there are no data on potential differences in clinical features between boys and girls hospitalized with RSV infection.
Methods
We compared the average population-based rates of hospitalization and the clinical features of the illness between boys and girls hospitalized with virologically confirmed RSV infection during 2006–2020 at Turku University Hospital, Finland. During this period, testing for RSV was routine in all children admitted with respiratory infections. The comparisons were performed in different age groups of children up to 5 years of age.
Results
Among all 1204 children < 5 years of age hospitalized with RSV, the average annual RSV hospitalization rates were 4.0/1000 in boys and 3.3/1000 in girls (incidence rate ratio [IRR] 1.21; 95% CI, 1.07–1.35; p = 0.001). The difference was greatest in children aged 3–23 months, among whom the corresponding rates were 5.4/1000 in boys and 3.6/1000 in girls (IRR, 1.50; 95% CI, 1.25–1.80; p < 0.001). The occurrence of respiratory distress was consistently higher in boys than in girls among children aged 6–17 months. In this group of 233 children, 128 of 141 (90.8%) boys had documented respiratory distress, compared with 70 of 92 (76.1%) girls (p = 0.002).
Conclusions
Except for the first 3 months after birth, boys have a 50% higher risk of RSV hospitalization than girls during the first 2 years of life. In that same age group, boys hospitalized with RSV have also significantly more respiratory distress than girls.